Surgical treatment of penoscrotal lymphedema in a patient with Milroy’s disease: case report - João Roberto Farias de Souza; Maria Luiza Marialva Rodrigues; Sérgio Antônio Saldanha Rodrigues Tamborini; Lívia Dornelas Côrrea; Clarissa Leite Turrer; Armando Chiari (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: Milroy disease manifests itself as lymphedema of the lower limbs and genital region, which causes physical and social damage. Case Report: A case of severe-scrotal lymphedema in a patient with Milroy disease. Surgical resection of the affected tissue and reconstruction with local flaps and skin graft were performed. Discussion: Milroy disease is a rare autosomal dominant disease. The clinical presentation is progressive and results from hypoplasia of the lymphatic vessels of the lower limbs. Treatment in advanced cases is mainly surgical. Conclusion: In the case of a patient with Milroy disease and severe penoscrotal lymphedema, surgical treatment is a good option. The use of parascrotal flaps for scrotoplasty associated with a graft to recover the penis provides a good functional result.